Additive impact of pre‐liver transplant metabolic factors on survival post‐liver transplant. Issue 5 (May 2016) - Adams, Leon A; Arauz, Oscar; Angus, Peter W; Sinclair, Marie; MacDonald, Graeme A; Chelvaratnam, Utti; Wigg, Alan J; Yeap, Sze; Shackel, Nicholas; Lin, Linda; Raftopoulos, Spiro; McCaughan, Geoffrey W; et al.
Abstract: Background and Aim: Diabetes at time of liver transplantation is associated with reduced post‐transplant survival. We aimed to assess whether additional metabolic conditions such as obesity or hypertension had additive prognostic impact on post‐transplantation survival. Methods: A multi‐center cohort study of 617 adult subjects undergoing liver transplantation between 2003 and 2009 has been used. Dry body mass index was calculated following adjustment for ascites. Results: After a median follow‐up of 5.8 years (range 0–10.5), 112 (18.2%) patients died. Diabetes was associated with reduced post‐transplant survival (hazard ratio 1.89, 95% confidence interval [CI] 1.25–2.86, P = 0.003), whereas obesity, hypertension, dyslipidemia, and the metabolic syndrome itself were not ( P > 0.3 for all). Patients with concomitant diabetes and obesity had lower survival (adjusted Hazard Ratio [aHR] 2.40, 95%CI 1.32–4.38, P = 0.004), whereas obese non‐diabetic patients or diabetic non‐obese patients had similar survival compared with non‐diabetic, non‐obese individuals. The presence of hypertension or dyslipidemia did not impact on survival in patients with diabetes ( P > 0.1 for both). Obese diabetic patients had longer intensive care and hospital stays than non‐obese diabetic or obese, non‐diabetic patients ( P < 0.05). The impact of concomitant obesity and diabetes on survival was greater in subjects aged 50+ years (52.6% 5‐year survival, aHR 3.04, 95% CI 1.54–5.98) or those transplanted with hepatocellular carcinoma (34.1% 5‐year survival, aHR 3.35, 95% CI 1.31–5.57). Diabetes without obesity was not associated with an increased mortality rate in these sub‐groups. Conclusions: Concomitant diabetes and obesity but not each condition in the absence of the other is associated with reduced post‐liver transplant survival. The impact of diabetes and obesity is greater in older patients and those with hepatocellular carcinoma.